Automatic aquaponic monitoring system / Affan Mohd Nazeri - Mohd Nazeri, Affan (2020)
Agricultural goods demand is gradually growing with the rise of the world population. However, because of climate change in the world, many plants are often damaged by the weather. Aquaponic which was introduced a long time ago, but it has become popular nowadays especially in Malaysia. It is one of suitable solution for the food security and sustainability, but when operate it manually it will require more time and labour force to keep monitor it. This research proposed an automatic aquaponic monitoring system which helps the owner to monitor the system through Blynk application on their smartphones. It helps users to monitor the temperature, humidity, light, water level in fish tank and water flow in the reservoir. The system also will notify the owner when any abnormal or failure occurs in the system which include the function of water pump, lamp, or exhaust fan. It also will automatically maintain the good surrounding for the crops. With this system, it will reduce labour cost and operation cost.